Alopecia and Hypotrichosis as Characteristic Findings in Woodhouse‐Sakati Syndrome: Report of a Family with Mutation in the C2orf37 Gene. Issue 1 (9th September 2013) - Nanda, Arti; Pasternack, Sandra M.; Mahmoudi, Hassnaa; Ishorst, Nina; Grimalt, Ramon; Betz, Regina C.
Abstract Woodhouse‐Sakati syndrome (WSS) is a rare autosomal recessive disorder characterized by alopecia, hypogonadism, diabetes mellitus, intellectual disability, sensorineural deafness, extrapyramidal signs, and low insulinlike growth factor 1 levels. Inter‐ and intrafamilial phenotypic variability have been reported. Mutations in the C2orf37 gene cause WSS. The present report describes the clinical signs and symptoms of three affected siblings from a consanguineous Bedouin family from Kuwait. Direct sequencing of the C2orf37 gene revealed that the c.436delC (p.Ala147Hisfs*9) mutation was present in a homozygous state in all affected siblings and in a heterozygous state in the parents and a healthy sister. Nine C2orf37 mutations causing WSS have been identified. This family shared the mutation reported earlier in Saudi families and families of Bedouin tribes from Qatar and Israel. No phenotypic or genotypic correlation has been observed. Despite the great phenotypic variability of WSS, hypotrichosis has been observed in all individuals with WSS reported. This condition has not been reported in the dermatologic literature. WSS should be included in the differential diagnosis of syndromic congenital hypotrichosis.